Resistência de genótipos de laranja doce (Citrus sinensis) ao cancro cítrico e diversidade genética de Xanthomonas citri subsp. citri - Gonçalves-Zuliani, Aline Maria Orbolato (2014)
Citrus canker caused by the bacterium Xanthomonas citri subsp. citri is one of the most important diseases of citrus. The use of resistant genotypes plays an important role in the management and control of the pathogen, being a viable measure for the producer and sustainable for the environment. The scope of this study was to evaluate citrus genotypes and its resistance to citrus canker in field, greenhouse and detached leaves, in addition to assessing the genetic diversity of Xanthomonas citri in commercial and experimental orchards of Paraná State, Brazil. 25 sweet orange genotypes of Pera variety were evaluated in three regions of Paraná State, Congonhinhas, Cornélio Procópio and Paranavaí, beyond the influence of rootstocks, Rangpur lime, sunki tangerine, cleopatra tangerine and caipira orange on them. Diagrammatic scales were used to assess the incidence and severity on leaves and fruits. These genotypes were evaluated in greenhouse conditions by inoculating the X. citri inoculum and measuring the lesions diameters. Citrus genotypes with different degrees of resistance were compared by using the methodology of artificially inoculated detached leaves. Furthermore genetic diversity of X. citri subsp. citri in commercial and experimental orchards of Paraná was verified by PCR analysis using microsatellite markers. Among the analyzed genotypes and in all evaluated sites, EEL Pera oranges and Ovale Siracusa stood out with more resistant to citrus canker on leaves and fruits. A similar situation occurred in greenhouse conditions for EEL genotype, which had the smallest diameter of lesion. The rootstock affected the resistance of Pera orange genotypes whereas plants grafted on caipira orange showed lower incidence and severity on leaves and fruits compared to grafted on Rangpur lime. The detached leaves methodology showed to be an important tool in the evaluation of citrus genotypes resistance to citrus canker, enabling the differentiation of the Pera IAC and Washington navel genotypes in relation to the lesions diameters. Pera IAC exhibited greater resistance to the pathogen, showing the smallest average of lesion diameter (1.32 mm), when compared to Washington navel (1.84 mm). This greater resistance demonstrated by Pera IAC may be related to lower stomatal density and increased release of toxic chemicals in the environment, being important physical and chemical barriers against aggressiveness of Xanthomonas citri. In studies of genetic diversity was observed that the origin and the host did not influence the differentiation among the isolates. Suggesting that populations of X. citri subsp. citri found in Parana are clonal, with strong epidemiological link.